Linguistic representation of time and space in Kazakh folklore genres - Lyazzat Yespekova, Gulbarshin Syzdykova, Zhantas Zhakupov, Lyazat Meirambekova, Zhanat Aimukhambet, Marzhan Akhmetova, (Opción, 2020)
The study aims to investigate the linguistic representation of time and space in Kazakh folklore genres by using the comparative-historical, historical-comparative approaches. The phenomena of folklore genre are reflected in such categories as space and time. Features of mythological time and space, epic time and space, fairy-tale time and space are expressed in language. Moreover, the national codes of the Kazakh folklore will be disclosed in the language representation of time and space. There is some evidence to support that this is a phenomenon of folklore.